ANALISA KASUS ATAS JUAL BELI TANAH WARISAN (STUDI KASUS PUTUSAN MA Nomor 680 K/PDT/2009) ANTARA ASTON PURBA DKK MELAWAN PATAR SIMAMORA DAN GOMAR PURBA - CLARA HELMY SIHITE (PREMISE LAW JURNAL, 2014)
ABSTRACT If the land is to be sold, all heirs of the testator must know and agree with the trading business. If one of the heirs of the testator does not know and does not agree with the trading business, the heir can cancel the trading business because he/she has the right to the inherited land. Based on this issue, this study was conducted to find out the consequence of the inherited land trading business without the knowledge or agreement of the other heirs in accordance with the Decision of the Supreme Court No. 680/K/Pdt/2009. The result of this study showed that the procedures of inherited land trading business which is in accordance with Agrarian Law were inherited land trading business must be agreed by all heirs as the party that received the right to land through inheritance, and they must make an underhanded agreement or notarial deed stating that all heirs agree to sell the inherited land. Legal consequence of the inherited land trading agreement unknown to the other heirs is that the agreement is unnulled by law because the trading business has inflicted loss to the other heirs. The judge’s consideration in the decision of the Supreme Court No. 680/K/Pdt/2009 was to protect the buyer with good faith because he/she has settled the price of the land he/she bought and has done his/her duty as a seller. Keywords: Trading, Inherited Land, Agrarian Law